A novel quartz fibre reinforced dense polyimide matrix composite: effect of preform stitching. (21st October 2019) - Bai, Huizhen; Sun, Xun; Liu, Haitao; Yang, Lingwei; Huang, Wenzhi; Wang, Zhen
ABSTRACT: A dense polyimide (PI) composite reinforced by quartz fibres (QFs), was prepared by vacuum assisted polymer infiltration and hot-pressing in this work. The microstructures and the mechanical properties of the as-fabricated composites were investigated. The results show a high flexural strength (≈686 MPa) of the composite, due to its dense nature. Moreover, there was no significant change in the bending strength of the stitched composites. The laminates mainly suffered delaminations and fracture of the QFs. The intralaminar bonding of the composite was enhanced by a novel stitching technique (all 28 layers stitched together by untwisted quartz filament tows in the plain stitch). As a result, the interlaminar fracture energy with 1 stitches cm −2 stitch density was increased by 87.1%, compared to that of the unstitched composite. In the case of stitched specimens, stitching plays an important role in improving the Gc and suppresses the influence of in-plane fibre orientation.